STUDY ON ELEVATION OF PARTIALLY REMOVABLE PROSTHESES IN SYSTEMIC CONTEXT IN GERIATRIC PATIENTS - Irina Gradinaru; Loredana Liliana Hurjui; Ion Hurjui; Magda-Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2019)
The quality of life is in to the close relationship with maintenance of oral health, part of general health which is affected or which influence, having in the end, a great impact on mental condition and integration. The aim of our study was to establish the main criteria for the choice of partially movable prostheses in geriatric patients in a systemic context. Material and method.The study was conducted on a group of 60 geriatric patients diagnosed with various forms of general pathology corroborated with various edentational forms presented on the basis of the Clinic of , Iasi. Education of the Faculty of Dental MedicineAll patients underwent a complex clinical examination , supported by paraclinical assessments. which allowed the establishment of a biological balance sheet.Results and discussions Following the subjective clinical examination (anamnesis and questionnaire), we identified 34% of cases with diabetes, 36% with cardiovascular pathology, 9% with respiratory pathology (COPD and Asthma), 10 % of cases with diabetes associated with HTA, 1 1% cases of digestive pathology (chronic gastritis, hepato-biliary pathology). Conclusions:The flexible dentures observe these criteria better than those of conventional acrylate. The implied patients prefer flexible acrylate at a rate of 100%